Integrated molecular landscape of amyotrophic lateral sclerosis provides insights into disease etiology. (6th March 2017) - Klemann, C.J.H.M.; Visser, J.E.; Van Den Bosch, L.; Martens, G.J.M.; Poelmans, G.
Abstract: Amyotrophic lateral sclerosis (ALS) is a severe, progressive and ultimately fatal motor neuron disease caused by a combination of genetic and environmental factors, but its underlying mechanisms are largely unknown. To gain insight into the etiology of ALS, we here conducted genetic network and literature analyses of the top‐ranked findings from six genome‐wide association studies of sporadic ALS (involving 3589 cases and 8577 controls) as well as genes implicated in ALS etiology through other evidence, including familial ALS candidate gene association studies. We integrated these findings into a molecular landscape of ALS that allowed the identification of three main processes that interact with each other and are crucial to maintain axonal functionality, especially of the long axons of motor neurons, i.e. (1) Rho‐GTPase signaling; (2) signaling involving the three regulatory molecules estradiol, folate, and methionine; and (3) ribonucleoprotein granule functioning and axonal transport. Interestingly, estradiol signaling is functionally involved in all three cascades and as such an important mediator of the molecular ALS landscape. Furthermore, epidemiological findings together with an analysis of possible gender effects in our own cohort of sporadic ALS patients indicated that estradiol may be a protective factor, especially for bulbar‐onset ALS. Taken together, our molecular landscape of ALS suggests that abnormalities within three interconnected molecular processes involved in the functioning and maintenance of motor neuron axons are important in the etiology of ALS. Moreover, estradiol appears to be an important modulator of the ALS landscape, providing important clues for the development of novel disease‐modifying treatments.